Osteoporosis in a murine model of postmenopausal lupus. (January 2020) - Nordqvist, J; Lagerquist, M K; Grahnemo, L; Koskela, A; Islander, U; Carlsten, H
Background/objective: Postmenopausal women with systemic lupus erythematosus have an increased risk of osteoporosis and associated fractures. Their increased osteoporosis risk is probably caused by a high level of inflammation, use of glucocorticoids, impaired kidney function, and early menopause as these are known risk factors for osteoporosis. Due to these risk factors and the lack of safe and effective treatments, new therapies for the treatment of osteoporosis in this group of patients are needed. Ovariectomized MRL/ lpr mice constitute a well-established model for studies of postmenopausal systemic lupus erythematosus; however, it is not clear to what extent this experimental model is associated with the development of osteoporosis. Thus, the aim of this study was to characterize the skeleton of ovariectomized MRL/ lpr mice to determine the suitability of this model in studies of prospective new therapies for osteoporosis in postmenopausal systemic lupus erythematosus patients. Methods: Skeletal parameters were measured in MRL/ lpr mice and MRL/++ control mice, using peripheral quantitative computed tomography, high-resolution micro-computed tomography and biomechanical analyses. mRNA expression of bone-remodeling markers was measured by quantitative polymerase chain reaction and serological markers of lupus disease were evaluated using ELISA. Results: Total bone mineral density was reduced in MRL/ lpr mice compared with MRL/++ mice and MRL/ lpr mice had reduced cortical and trabecular bone thickness compared with MRL/++ mice. In line with the low bone mass of MRL/ lpr mice, gene expression analysis of cortical bone from these mice indicated an increased osteoclast activity as well as a decreased osteoblastogenesis and osteoblast activity, compared with MRL/++ mice. Conclusion: Ovariectomized MRL/ lpr mice constitute a valuable experimental model for studies of osteoporosis development in postmenopausal systemic lupus erythematosus and this model is thus suitable for future studies of osteoporosis treatment in systemic lupus erythematosus.